Angiosarcoma of breast and chest wall complicated with tuberculous empyema: A case report - Xingchen Gao; Haiyan Liu; Feng Wang; Ziwei Xu; Yi Han; Shuku Liu (Thoracic Cancer, 2022)
Abstract Angiosarcoma is a highly malignant endothelial tumor, accounting for 1% to 2% of soft tissue sarcomas. The most common site of the disease is the skin, accounting for approximately 60% of cases, especially the skin of the head. It can also occur in soft tissue, bone, and retroperitoneum. However, angiosarcomas of the breast and chest wall are rare. Here, we report a 44‐year‐old woman who was admitted to hospital with encapsulated empyema. She was subsequently diagnosed with angiosarcomas of the breast and chest wall with tuberculous empyema. At the same time, we also reviewed the current research progress in angiosarcoma of the breast and chest wall to explore better treatment options for these patients.